LOCAL CULTURE-BASED VOCATIONAL SCHOOL IN PALEMBANG POST COVID 19: LEARNING MANAGEMENT, CHALLENGES AND CURRICULUM DEVELOPMENT POTENTIAL - Maya NS; Arif Rahman; Sayid Habiburrahman (Jurnal Ekonomi, 2022)
This study wants to highlight the learning of post-Covid-19 vocational schools in Palembang, especially how to re-accommodate local culture as an integrated part of learning in schools.The significant impact of the pandemic on vocational education over the past two years has hampered various courses of learning in schools.Here, there are three aspects that will be explored, namely in terms of education management, future challenges and potential for curriculum development after Covid 19.This study is a qualitative research, research data collected from the results of the literature, interviews and documentation.Then the data is interpreted through descriptive analysis.The results of the study indicate that vocational schools face the uncertainty of the situation as a challenge in making changes to adaptive learning formats.Such conditions open up opportunities for the development of a responsive and more flexible curriculum to accommodate local culture as part of learning in vocational schools.